Pb10O4(BO3)3I3: a new noncentrosymmetric oxyborate iodide synthesized by the straightforward hydrothermal method. Issue 40 (1st August 2019) - Zhou, Jinjie; Wu, Hongping; Yu, Hongwei; Hu, Zhanggui; Wu, Yicheng
Abstract : A new first reported oxyborate iodide Pb10 O4 (BO3 )3 I3 has been synthesized by a straightforward hydrothermal method. Abstract : Borate iodide has interesting functional properties but is challenging for synthesizing. A new non-centrosymmetric borate iodide Pb10 O4 (BO3 )3 I3 has been synthesized by a straightforward hydrothermal method. Pb10 O4 (BO3 )3 I3 crystallizes in the noncentrosymmetric monoclinic space group Cc . In its structure, the basic structural building units [Pb10 O8 ] connect with BO3 groups to form two-dimensional (2D) [Pb10 O8 B2 O6 ]∞ layers stacked along the b -axis, which are further linked by the B(1)O3 groups to constitute a 3D framework. Interestingly, in this structure, some oxygen atoms are coordinated by four Pb 2+ cations to form [OPb4 ] groups, rather than directly connecting with B 3+ cations. Therefore, this compound belongs to a new type of borate iodide, oxyborate iodide. To the best of our knowledge, this is the first reported oxyborate iodide. In addition, its functional properties including second harmonic generation (SHG) response, UV-vis-NIR diffuse reflectance and IR spectra were also investigated. The origin of the SHG effect was studied by dipole moment calculations and structure comparison.